Predicting injury risk in young female volleyball players through movement and jump assessments - Erol, Mustafa; Girginer, Fatma Gozlukaya; Seyhan, Sinan; Acar, Gorkem; Cerit, Gunay; Uzun, Meliha; Soylu, Caglar (Frontiers in Public Health, 2025)
BackgroundThe increasing prevalence of sports injuries among young female volleyball players, driven by biomechanical and hormonal factors, necessitates effective prevention strategies. Screening tools like the Functional Movement Screen (FMS) and Star Excursion Balance Test (SEBT) often show inconsistent predictive validity for injury risk in this population. This study investigates associations between FMS, SEBT, agility, and muscle strength with injury risk in young female volleyball players to refine prediction models and inform targeted interventions.MethodsA cross-sectional, observational study involved 30 female volleyball players (aged 14–18 years, mean age 16.2 ± 1.3 years, mean volleyball experience 3.5 ± 1.1 years) from a Turkish amateur club. Assessments occurred over 2 days after a 5-min warm-up, with 2-min rests between trials, conducted by trained evaluators. On day one: (1) Functional Movement Screen (FMS), scoring seven movement patterns (0–21); (2) Star Excursion Balance Test (SEBT), measuring reach in eight directions, normalized to leg length. On day two: (3) Agility t-test, a timed T-shaped course; (4) Countermovement Jump (CMJ), recording the highest of three jumps.ResultsSignificant differences emerged in FMS scores (p = 0.0012), SEBT anterior asymmetry (p < 0.0001), and CMJ heights (p = 0.0198) across risk groups, with LR (n = 5) showing superior performance (FMS M = 15.4 ± 0.9, CMJ M = 38.2 ± 3.3 cm) versus HR (n = 9, FMS M = 10.8 ± 2.1, CMJ M = 27.2 ± 8.9 cm). A moderate negative correlation (r = −0.41, p = 0.0236) between FMS and SEBT asymmetry, and positive correlations with anterior reach (r = 0.37–0.45, p < 0.05), were noted. High-risk athletes (n = 18) were taller (M = 174.2 ± 5.8 cm, p = 0.0013) and showed a 4.2-fold increased risk with FMS ≤ 14 and CMJ < 30 cm (OR = 4.20, p = 0.0158), with combined FMS/SEBT predicting risk with 89% accuracy (AUC = 0.89, p < 0.0001).ConclusionFMS scores, SEBT asymmetry, and CMJ heights effectively predict injury risk in young female volleyball players, with thresholds (FMS ≤ 14, SEBT ≥4 cm, CMJ < 30 cm) guiding targeted interventions. The study’s focus on gender-specific risks and height-related biomechanics offers a foundation for tailored prevention programs, reducing healthcare costs and promoting equitable sports participation, aligning with global health priorities.